THE GLOBAL FINANCIAL CRISES AND THEIR TYPES - E. V. Vasina (Vestnik MGIMO-Universiteta)
In this study the author reveals the essence of the financial crisis and examines the various types of financial crises. By studying the literature on financial crises, the author of the studypays attention to three specific areas: the definition of the crisis, the manifestations of the crisis and the types of financial crises. The article notes that the term "financial crisis" is widely used in a variety of situations in which some financial assets suddenly lose most of their nominal value, but it does not necessarily lead to changes in the real economy. The financial crisis is a crisis that is systematically covers financial markets and institutions of the financial sector, international finance, money circulation and credit, state, municipal and corporate finance. Financial crises have common elements, but they come in different forms. Financial crises are generally multidimensional events and are difficult to characterize using a single indicator. The author considers the following types of financial crises: a banking crisis, a currency crisis, speculative bubbles and international financial crises. Banking crisis is a situation when a bank faces with a sudden outflow of depositors' funds. A currency crisis is a situation when the exchange rate, which is pegged to the currency of another country, is on the verge of collapse, causing committed speculation. A speculative bubble is in the case of large, sustainable overpricing of any asset class. Financial crises are reflected in a sharp rise in interest rates, a collapse in exchange rates, massive withdrawal of deposits from banks and credit crunch, currency and debt crisis.